Philosophy as an Art of Living. An interpretation of Confucianism from an Aesthetic Approach. - Luque-Moya, Gloria (My University, 2023)
Confucian philosophy is often regarded as a moral tradition and closely identified with a small set of ethical concepts that assumed a limited interpretation of a long-standing tradition. However, we can reconsider Confucianism as a school of thought concerned with the interaction of specific people in particular contexts, which entails human creative dimension. The aim of this presentation is to provide an analysis of the reinvention in Confucian tradition from its origins. Confucius rejects the idea of a fixed order, and instead emphasizes that the world, as well as our interactions, are constantly changing. For that reason, philosophy also needs to change and be reinvented.
Keywords: Confucianismo; Confucius; Creativity; Art of living; Aesthetics; Modus vivendi